2006
DOI: 10.1177/1524839906287055
|View full text |Cite
|
Sign up to set email alerts
|

Community Coalitions to Control Chronic Disease: Allies Against Asthma as a Model and Case Study

Abstract: There is a rich and extensive literature regarding coalitions as vehicles for amassing resources, influence, and energy in pursuit of a health goal. Despite insufficient empirical data regarding outcome, a number of observers have posited the aspects of coalition processes thought to lead to goal attainment. The supplement, which this article is part of, is devoted to an examination of how these elements fitted together (or did not) in the seven areas across the United States where Allies coalitions devoted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 10 publications
0
45
0
Order By: Relevance
“…Fisher et al 27 evaluated a neighborhood asthma coalition in St Louis and found a significant decrease in acute care rates for asthma among families with high levels of participation in coalition activities. Assessing 7 asthma coalitions across the United States, Clark et al 28 found that these partnerships achieved several system and policy changes. Two established community-wide patient registries.…”
Section: Community Coalitions and Partnershipsmentioning
confidence: 99%
“…Fisher et al 27 evaluated a neighborhood asthma coalition in St Louis and found a significant decrease in acute care rates for asthma among families with high levels of participation in coalition activities. Assessing 7 asthma coalitions across the United States, Clark et al 28 found that these partnerships achieved several system and policy changes. Two established community-wide patient registries.…”
Section: Community Coalitions and Partnershipsmentioning
confidence: 99%
“…The CAACP drew heavily upon previous community-level, disease-specific projects, 14,15 particularly the design and experience of the Allies Against Asthma (Allies) Initiative, which was planned and implemented between January 2000 and July 2006 16 with funding from the Robert Wood Johnson Foundation and direction and technical assistance from the University of Michigan School of Public Health. Allies supported the development of seven community-based coalitions of professional and grassroots leaders to improve asthma care and coordination, and used standardized tools to evaluate coalition functioning and progression through previously described stages of coalition development.…”
Section: The Controlling Asthma In American Cities Projectmentioning
confidence: 99%
“…Influences that will affect the coalition's functioning and success include the cultural, political, and economic environment of the community; the history of collaboration; the presence of other coalitions; degree of cooperation and conflict among community agencies, geography, population diversity; and economic climate (Butterfoss & Kegler, 2002;Clark et al, 2006 [this issue]; Kenney & Sofaer, 2000;Lasker et al, 2001;McLeroy et al, 1994;Roussos & Fawcett, 2000;Wolff, 2001). Community readiness or preparedness for collaboration is another important dimension of community context and involves the ability of the community to take on its tasks and find ways to solve its own problems, usually involving multiple sectors (Wolff, 2001).…”
Section: Figure 1 Allies Against Asthma Cross-site Evaluationmentioning
confidence: 99%
“…A brief description of each coalition's primary interventions can be found in Appendix B, and a summary table found in the accompanying article by Clark et al (2006). Data regarding these activities have been gathered throughout the implementation period using Program Reach, a computerized Web-based tracking system, as described more fully below.…”
Section: Figure 1 Allies Against Asthma Cross-site Evaluationmentioning
confidence: 99%